Kazniva dejanja zoper delovno razmerje in socialno varnost - Filipčič, Katja (Podjetje in delo, 2016)
Dealing with criminal offences against labour relations raises numerous questions: what are prohibited consequences, the effect of objective impossibility of employer to pay prescribed obligations, the characteristics of criminal liability, the question of employee's consent to the reduction of his rights, unsolved problems with the liability for graver consequences. Prosecutors and judges are, due to a large increase in number of cases, confronted with these questions, and some of them do not yet have satisfactory answers.
Keywords: delodajalci; delovno pravo; kazniva dejanja; odgovornost; pravice; socialna varnost; socialno pravo